Manajemen risiko pembiayaan pada perbankan syariah: strategi dan tantangan di era modern - Aini, Kurrotul (Maliki Interdisciplinary Journal, 2026)
Islamic banking institutions in Indonesia are currently facing various complex challenges in managing financing risks, particularly in the contemporary era characterized by rapid digital transformation and the emergence of competitors from the financial technology (fintech) sector. This paper aims to examine various strategic approaches used in financing risk mitigation and to identify the main obstacles that arise during the implementation process. Employing a qualitative literature review method that examines case studies from Bank Syariah Indonesia (BSI), Erahn.id (a fintech company operating in the sharia pawnshop sector), and various relevant regulations, this article finds that the main risk mitigation strategies include the implementation of the risk management cycle (identification, measurement, monitoring, and control), restructuring of non-performing financing, and strengthening collateral analysis procedures. Significant obstacles identified include vulnerability to technology risks and cyberattacks, limited capacity of human resources proficient in both sharia principles and technology, liquidity pressures triggered by the digitalization of services, and challenges in ensuring compliance with sharia principles in digital transactions (such as elements of gharar and riba). This article concludes that financing risk management serves not merely as a mechanism to reduce potential losses, but rather as a critical strategic framework to ensure business sustainability, compliance with sharia values, and the competitiveness of the Indonesian Islamic banking industry in the modern era.